2011
DOI: 10.1371/journal.pone.0022718
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Immune Responses to Nine Mycobacterium tuberculosis Vaccine Candidates following Intranasal Vaccination

Abstract: BackgroundThe identification of Mycobacterium tuberculosis vaccines that elicit a protective immune response in the lungs is important for the development of an effective vaccine against tuberculosis.Methods and Principal FindingsIn this study, a comparison of intranasal (i.n.) and subcutaneous (s.c.) vaccination with the BCG vaccine demonstrated that a single moderate dose delivered intranasally induced a stronger and sustained M. tuberculosis-specific T-cell response in lung parenchyma and cervical lymph nod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 67 publications
(85 reference statements)
1
33
0
1
Order By: Relevance
“…Subsequently, immunization with 3 doses of apa was shown to be highly immunogenic in a murine model (36). Recently, among the nine M. tuberculosis recombinant proteins evaluated, the Apa antigen was found to be highly antigenic following BCG vaccination (37). Our data on heterologous prime-boost immunization also confirmed this immunogenicity induced by Apa, after an intratracheal M. tuberculosis infection, and showed that this immunization lasts longer than the one conferred by BCG vaccination alone.…”
Section: Discussionsupporting
confidence: 70%
“…Subsequently, immunization with 3 doses of apa was shown to be highly immunogenic in a murine model (36). Recently, among the nine M. tuberculosis recombinant proteins evaluated, the Apa antigen was found to be highly antigenic following BCG vaccination (37). Our data on heterologous prime-boost immunization also confirmed this immunogenicity induced by Apa, after an intratracheal M. tuberculosis infection, and showed that this immunization lasts longer than the one conferred by BCG vaccination alone.…”
Section: Discussionsupporting
confidence: 70%
“…Nonetheless, the ability of rApa to impart protection in this study is consistent with previous observation that i.n. subunit vaccination using rApa protein imparts notable protection in mice [18].…”
Section: Discussionmentioning
confidence: 99%
“…These mannose residues are absent in the recombinant form of Apa (rApa) expressed in E. coli , and the rApa is poorly recognized by T cells of BCG inoculated guinea pigs [14], [15]. We and others have identified Apa as a possible vaccine candidate against TB [16][18], but the role of glycosylation in inducing protective T cell immunity had not been studied.…”
Section: Introductionmentioning
confidence: 99%
“…The body's immune system, possess the capacity, to stop the bacteria to reproduce continually. Thus, the immune system can make the lung infection inactive (dormant state) [7]. On the other hand, if the body's immune system is not strong enough and cannot contain the TB bacteria, then the bacteria will reproduce (become active or reactivate) in the lungs and spread elsewhere in the body.…”
Section: Signs and Symptoms Of Tuberculosismentioning
confidence: 99%